NANO silicon, NANO silicon-containing slurry, active substance for secondary battery, method for producing NANO silicon-containing slurry, and method for producing active substance for secondary battery

By controlling oxidation through controlled wet grinding and baking, nanosilicon is produced for secondary batteries, enhancing battery capacity and efficiency.

JP2025010003APending Publication Date: 2025-01-20DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024103917
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2024-06-27
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing silicon oxycarbide composites face issues with low retention rates and high oxidation when increasing Si content, leading to poor performance and short lifespan.

Method used

The production process involves controlled wet grinding of nanosilicon to reduce oxidation, using specific Si-NMR ratios and oxide film thickness, and incorporating it into a slurry with a dispersion liquid, followed by baking to form a high-performance active material for secondary batteries.

Benefits of technology

The method results in improved overall battery capacity, initial efficiency, and cycle maintenance rate, with nanosilicon exhibiting excellent charge-discharge characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010003000001_ABST
    Figure 2025010003000001_ABST
Patent Text Reader

Abstract

To provide a nano silicon totally high in a battery capacity, an initial efficiency, and a cycle maintenance rate by controlling a degree of oxidation of a nano silicon dispersed in a silicon material low, also excellent in balance of them, and useful as a high performance anode activation substance, a nano silicon-containing slurry, and a method for producing the same.SOLUTION: A nano silicon of the present invention has a ratio ((i) / (ii) ratio) of an area (i) of peaks in a range of -75 to -85 ppm to a total peak area (ii) of an area of peaks in a range of -110 to -100 ppm, an area of peaks in a range of -75 to -65 ppm, an area of peaks in a range of -40 to -30 ppm, an area of peaks in a range of -10 to 0 ppm, and an area of peaks in a range of -20 to -10 ppm is 0.4 or higher in 29Si-NMR.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nanosilicon, a nanosilicon-containing slurry, an active material for a secondary battery, a method for producing a nanosilicon-containing slurry, and a method for producing an active material for a secondary battery. [Background technology]

[0002] In recent years, the demand for small, high-capacity secondary batteries has increased with the spread of mobile electronic devices such as smartphones. Among these, secondary batteries such as lithium-ion batteries (sometimes written as LIB) have been rapidly deployed in electric vehicles (EVs), and the range of industrial use is expanding. Carbon-based graphite active materials (natural and artificial) are widely used as negative electrode materials for such secondary batteries, but the theoretical capacity density of graphite is low (372 mAh / g), and the battery capacity is close to its theoretical limit due to advances in battery construction technology.

[0003] In order to increase the capacity and energy density of lithium-ion secondary batteries, active materials made of silicon-based materials using silicon alloyed with lithium ions and their oxides have been studied. Among them, silicon oxycarbide (hereinafter sometimes referred to as SiOC) is a material composed of a ceramic skeleton composed of Si, O, and C and free carbon, and has attracted attention for its excellent charge / discharge cycle characteristics compared to other types of high-capacity active materials. For example, Patent Document 1 discloses a SiOC composite material in the form of fine particles, in which the fine particles are formed of an amorphous SiOC matrix having 20 to 60% by weight of Si, 20 to 40% by weight of O, and 10 to 50% by weight of C based on the total weight of the SiOC matrix, silicon particles are embedded in the SiOC matrix, and the fine particles are formed of the amorphous SiOC matrix, and the SiOC composite material has a core / coating structure having a core coated with at least one type of amorphous carbon layer. Patent Document 2 discloses a silicon-based nanoparticle having a BET specific surface area of ​​20 m2 and a SiOC coating layer containing at least one silicon-based nanoparticle and at least Si, O, and C as constituent elements. 2 / g or less, and the cumulative 10% particle size (D10), 50% particle size (D50), and 90% particle size (D90) are 1 nm≦D50≦990 μm, and D90 / D10≦13.0. Patent Document 3 also describes a SiOC structure having an average particle size (D50) of 0.01 to 0.6 μm, an average particle size (D90) of 0.01 to 1.0 μm, and a BET specific surface area according to the BET method of 40 to 300 m 2 / g, and the oxygen content is 10% by weight or more and less than 20% by weight. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2018-502029 [Patent Document 2] International Publication No. 2020 / 179409 Brochure [Patent Document 3] JP 2021-180124 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0005] In the above Patent Documents 1 to 3, in the silicon oxycarbide composite, increasing the Si content reduces the retention rate, which is an issue in improving performance. In addition, the degree of oxidation of the silicon particles cannot be sufficiently reduced, and although the initial capacity is high, the retention rate is low and the battery life is short.

[0006] In view of the above situation, the problem that the present invention aims to solve is to provide nanosilicon, a nanosilicon-containing slurry, an active material for secondary batteries, and a method for producing the same, which are useful as an active material for high-performance secondary batteries, by controlling the degree of oxidation of nanosilicon dispersed in a silicon material to be low, thereby achieving high overall battery capacity, initial efficiency, and cycle retention rate, and also having an excellent balance between these. [Means for solving the problem]

[0007] In order to solve the above problems, the inventors discovered that by improving the mechanical means of wet grinding during the production of nanosilicon, the degree of oxidation of nanosilicon can be reduced, resulting in the development of the present invention, which demonstrates excellent charge / discharge characteristics when used as an active material for secondary batteries.

[0008] That is, the present invention is as follows. [1] 29 Nanosilicon in which the ratio (i) of the area of ​​the peak in the range of -75 to -85 ppm to the total peak area (ii) of the areas of the peaks in the ranges of -110 to -100 ppm, -75 to -65 ppm, -40 to -30 ppm, -10 to 0 ppm, and -20 to -10 ppm [(i) / (ii) ratio] in Si-NMR is 0.4 or more. [2] After calcination of the nanosilicon described in [1] 29 Nanosilicon having a ratio (iii) of the area of ​​the peak in the range of -110 to -100 ppm to the total peak area (iv) of the peak area in the range of -75 to -85 ppm and the peak area in the range of -95 to -85 ppm [(iii) / (iv) ratio] of 0.4 or less in Si-NMR. [3] The nanosilicon according to [1] or [2], wherein a portion of the oxide film on the outer surface of the nanosilicon is amorphous, and the maximum thickness of the oxide film is less than 20 nm. [4] Nanosilicon according to any one of [1] to [3], having a crystal orientation degree of 0.25 or more in the (111) plane. [5] A nanosilicon-containing slurry comprising the nanosilicon according to any one of [1] to [4] and a dispersion liquid. [6] An active material for secondary batteries, comprising the nanosilicon according to any one of [1] to [4]. [7] A method for producing a nanosilicon-containing slurry, comprising wet-pulverizing a silicon raw material to obtain a nanosilicon-containing slurry, wherein beads of 0.5 mm or less are used in the wet-pulverization, and the cumulative input power per weight during the wet-pulverization is 10,000 kWh / t or more. [8] A method for producing a nanosilicon-containing slurry according to [7], wherein the wet grinding is carried out in two or more stages by changing the bead diameter, and the ratio (D1 / D2) of the bead diameter D1 of the first stage to the bead diameter D2 of the second stage or later is 1.5 or more. [9] The specific surface area of ​​the silicon raw material is 30 m 2 / g or less.

[10] The true density of the beads is 6.5 g / cm 3 The method for producing a nanosilicon-containing slurry according to any one of the following items [7] to [9].

[11] The method for producing a nanosilicon-containing slurry according to any one of [7] to

[10] , wherein the volume filling rate of the beads in the bead mill in the wet pulverization is 50 to 95%.

[12] The method for producing a nanosilicon-containing slurry according to any one of [7] to

[11] , wherein the peripheral speed of a bead mill in the wet pulverization is less than 20 m / s.

[13] The method for producing a nanosilicon-containing slurry according to any one of [7] to

[12] , wherein the wet pulverization is carried out at a bead mill integrated input power per unit amount of silicon raw material within the range of 7500 kWh / t to 45000 kWh / t.

[14] A method for producing an active material for a secondary battery, comprising drying a mixture containing nanosilicon obtained by the method for producing a nanosilicon-containing slurry described in any one of [7] to

[13] and a resin, and firing the mixture in an inert gas atmosphere to obtain an active material for a secondary battery. Effect of the Invention

[0009] When the nanosilicon of the present invention is used as a negative electrode active material, the battery capacity, initial efficiency, and cycle retention rate are all high, and the balance between them is also excellent. In addition, the method for producing the nanosilicon-containing slurry of the present invention can efficiently produce the nanosilicon of the present invention. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a chart of the 29Si-NMR spectrum of the nanosilicon dry product 1 of Example 1. [Diagram 2] FIG. 2 is a chart of the crystal structure analysis (XRD) of the dried nanosilicon material 1 of Example 1 by the X-ray diffraction method. [Diagram 3] FIG. 3 is an HR-TEM image of the electrode film of Example 1. [Figure 4] FIG. 4 is an HR-TEM image of the electrode film of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Nanosilicon] The nanosilicon of the present invention is 29 In Si-NMR, the ratio (i) of the area of ​​the peak in the range of -75 to -85 ppm to the total peak area (ii) of the peak areas in the ranges of -110 to -100 ppm, -75 to -65 ppm, -40 to -30 ppm, -10 to 0 ppm, and -20 to -10 ppm [(i) / (ii) ratio] is 0.4 or more.

[0012] The nanosilicon of the present invention 29The mechanochemical reactants derived from bonds such as Si (zero valence) detected by Si-NMR and SiO4, SiO3C, SiO2C2, SiOC3, and SiC4 contribute to the formation of an oxide film on the Si surface by mixing nanosilicon and resin and baking them, and have a significant effect on the capacity and initial efficiency of the negative electrode active material. The peak in the range of -75 to -85 ppm is derived from Si (zero valence), and the above peak area (i) represents the proportion of Si (zero valence). In addition, the peak in the range of -75 to -65 ppm, the peak in the range of -40 to -30 ppm, the peak in the range of -10 to 0 ppm, and the peak in the range of -20 to -10 ppm are derived from Si (other than zero valence) such as SiO4, SiO3C, SiO2C2, SiOC3, and SiC4, and the total peak area (ii) represents the proportion of mechanochemical reactants other than zero valence. The peak area ratio (ii) / (i) of 0.4 or more indicates that the mechanochemical reaction products can be reduced, and the initial efficiency when used as a negative electrode active material is approximately 80% or more. The (ii) / (i) ratio is preferably 0.5 or more, more preferably 0.6 or more. The (ii) / (i) ratio is preferably higher, so there is no particular upper limit.

[0013] The nanosilicon of the present invention is preferably a nanosilicon-containing slurry dried at room temperature in vacuum to prevent oxidation of the nanosilicon itself. For example, when dried at a high temperature of 100°C or higher or in an atmosphere containing oxygen, oxidation of the nanosilicon itself is likely to progress, and the above (i) / (ii) ratio often becomes less than 0.4. In addition, drying at room temperature in vacuum usually requires a drying time of 10 hours or more. The above nanosilicon-containing slurry is as described below.

[0014] Nanosilicon which is the fired product of the nanosilicon of the present invention (hereinafter referred to as fired nanosilicon) 29In the Si-NMR measurement, it is preferable that the ratio (iii) of the peak area in the range of -110 to -100 ppm to the total peak area (iv) of the peak areas in the ranges of -75 to -85 ppm and -95 to -85 ppm [(iii) / (iv) ratio] is 0.4 or less.

[0015] The peak in the range of -110 to -100 ppm is derived from SiO4, and the peak area (iii) represents the proportion of silicon dioxide. The peak in the range of -95 to -85 ppm is derived from Si, and the peak area (iv) represents the proportion of zero-valent silicon. Therefore, when the (iii) / (iv) ratio is 0.4 or less, nanosilicon with reduced oxidation is obtained. The (iii) / (iv) ratio is preferably 0.3 or less, and more preferably 0.2 or less. The (iii) / (iv) ratio is preferably as low as possible, and the lower limit is not particularly limited, but is, for example, 0.01.

[0016] In order to remove the dispersant that remains in the nanosilicon of the present invention even after drying, the nanosilicon of the present invention is preferably calcined, for example, at 1050 to 1100°C in a nitrogen atmosphere for 4 to 8 hours. If a normal organic dispersant is used, it can be completely removed under these calcination conditions. The calcined nanosilicon is nanosilicon without a dispersant, and the calcined nanosilicon 29 Si-NMR was observed for nanosilicon without any dispersant.

[0017] 29 The Si-NMR spectrum can be easily obtained using a solid-state NMR device, and the solid-state NMR measurement of the present invention can be performed using, for example, a device (JNM-ECA600) manufactured by JEOL Ltd. The above peak area ratios [(ii) / (i) and (iii) / (iv)] are obtained by performing single pulse measurement with a solid-state NMR analyzer, Fourier transforming the obtained solid-state NMR spectrum data, and performing waveform separation using the Gauss+Lorentz function. Next, the ratios are calculated based on the peak areas of the peaks in each chemical shift value (ppm) range obtained by waveform separation.

[0018] The nanosilicon of the present invention has an oxide film on its outer surface that is partly amorphous, and the maximum thickness of the oxide film is preferably less than 20 nm. The oxide film is a coating of a metal oxide, and the type of metal oxide is not particularly limited, but examples thereof include silicon oxide, titanium oxide, manganese oxide, alumina, zinc oxide, and nitrogen oxide, and is preferably silicon oxide. The maximum thickness of the oxide film is preferably less than 15 nm, more preferably less than 10 nm, and particularly preferably 5 nm or less. When the thickness of the oxide film is within the above range, the oxidation of the nanosilicon can be suppressed without preventing the conduction of lithium ions and the transition of electrons during charging and discharging when used as a negative electrode active material. The thickness of the oxide film can be measured, for example, by observing the nanosilicon with a transmission electron microscope (HR-TEM).

[0019] The nanosilicon of the present invention is prepared by vacuum drying a nanosilicon-containing slurry at room temperature to produce a dried nanosilicon, and then calcining the dried nanosilicon at 500°C in a nitrogen atmosphere for 1 hour to produce calcined nanosilicon. When the total amount of the calcined nanosilicon is taken as 100% by mass, the weight of oxygen is, for example, 15% by mass or less (proportion of oxygen in the calcined nanosilicon, oxygen concentration), preferably 12% by mass or less, and more preferably 9% by mass or less. The reason for producing the calcined nanosilicon by calcining the dried nanosilicon is to evaluate the oxidation of the nanosilicon by removing the dispersant. By reducing the weight of oxygen as described above by the production method of the present invention, when the material is used as an active material for a secondary battery, the material exhibits excellent charge / discharge characteristics in terms of capacity and initial charge / discharge efficiency.

[0020] The oxygen concentration can be measured using an oxygen / nitrogen / hydrogen analyzer (for example, ONH836 type manufactured by LECO Corporation).

[0021] The specific surface area of ​​nanosilicon is 100 to 400 m 2 The specific surface area is preferably 100 to 300 m / g. The specific surface area is a value determined by the BET method and can be determined by nitrogen gas adsorption measurement, for example, by using a specific surface area measuring device. From the viewpoint of electric capacity and initial coulombic efficiency, the specific surface area of ​​nanosilicon is preferably 100 to 300 m 2 / g is more preferable, and 100 to 250m 2 / g is more preferred.

[0022] The value obtained by dividing the oxygen concentration of the nanosilicon fired product by the specific surface area of ​​nanosilicon, that is, the oxygen concentration per specific surface area of ​​nanosilicon, is preferably 0.1 or less, more preferably 0.05 or less, and further preferably 0.01 or less.

[0023] The degree of crystal orientation of the (111) plane of the nanosilicon of the present invention is preferably 0.25 or more. The degree of crystal orientation is more preferably 0.35 or more, and particularly preferably 0.45 or more. When the degree of crystal orientation is within this range, the nanosilicon has a flat shape, the degree of oxidation can be reduced, and the expansion of silicon during charging and discharging can be suppressed, so that when used as an active material for secondary batteries, it exhibits excellent charge and discharge characteristics such as capacity, initial charge and discharge efficiency, and retention rate.

[0024] The degree of crystal orientation can be measured using an X-ray crystal structure analyzer (Cu-Kα). In detail, the degree of crystal orientation can be calculated by determining the crystallite size based on the full width at half maximum (FWHM) using the Scherrer method described below. L = Kλ / (βcosθ) K: shape factor, λ: X-ray wavelength, β: peak half-width (in radians), θ: Bragg angle, L: crystallite size

[0025] The nanosilicon of the present invention may be in a particulate form such as a sphere or a spheroid, or in a sheet form such as a cube, or may be in a flat form having a minor axis and a major axis, and its shape is not particularly limited. When it is in a particulate form, the volume average particle diameter (d50) is, for example, 10 to 200 nm, preferably 10 to 100 nm, and more preferably 20 to 80 nm. If the volume average particle diameter (d50) of the nanosilicon is 200 nm or less, the pulverization phenomenon during charging and discharging is unlikely to occur, and the charge and discharge performance of the active material can be improved. In addition, if the volume average particle diameter (d50) of the nanosilicon is 10 nm or more, the aggregation of nanosilicon can be suppressed, and the nanosilicon can be uniformly dispersed in the active material. In addition, the surface activity energy of the nanosilicon can be reduced, and the generation of by-products on the surface of the nanosilicon during high-temperature baking of the active material can be suppressed, leading to improved charge and discharge performance. The volume average particle size (d50) can be measured by a dynamic light scattering method using a laser particle size analyzer or the like.

[0026] In addition, when the nanosilicon has a flat shape, the major axis is, for example, 50 to 300 nm, preferably 70 to 250 nm, more preferably 100 to 200 nm, and the minor axis is, for example, 1 to 100 nm, preferably 3 to 80 nm, more preferably 5 to 50 nm. In addition, the aspect ratio (major axis / minor axis) is, for example, 1 to 100, preferably 1.5 to 50, more preferably 2.0 to 30. By keeping the major axis, minor axis, and aspect ratio within the above ranges, the degree of oxidation of the nanosilicon can be controlled low, and the charge / discharge characteristics such as the battery capacity and initial efficiency can be improved. The shape of the nanosilicon can be measured by a dynamic light scattering method, but by using an analysis means such as a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM), the sample sizes such as the major axis and minor axis can be measured more easily and precisely. In the case of negative electrode active materials containing nanosilicon, the sample can be cut with a focused ion beam (FIB) and the cross section can be observed with a FE-SEM, or the sample can be sliced ​​and the shape of the nanosilicon can be measured by TEM observation.

[0027] [Nanosilicon-containing slurry] The nanosilicon-containing slurry of the present invention includes the nanosilicon of the present invention and a dispersion liquid. That is, the nanosilicon of the present invention is dispersed in a liquid to form a slurry. The dispersion liquid may be either an aqueous solvent or a non-aqueous solvent, but a non-aqueous solvent is preferred. The nanosilicon-containing slurry of the present invention may contain other components such as various additives, silane coupling agents, antifoaming agents, leveling agents, and viscosity adjusters in addition to the nanosilicon and the dispersion liquid.

[0028] (Dispersion liquid) Examples of the aqueous solvent include water and alcohol-based solvents. Examples of the non-aqueous solvent include hydrocarbon-based, ketone-based, ester-based, and ether-based solvents. Among them, ketone-based solvents such as MEK (methyl ether ketone) are preferred because they can suppress the oxidation of the nanosilicon surface. The ratio of these dispersions is preferably 50 to 1000 parts by mass, more preferably 100 to 500 parts by mass, relative to 100 parts by mass of nanosilicon. The nanosilicon-containing slurry of the present invention preferably contains a non-aqueous solvent in such a ratio that the viscosity and non-volatile content at 110°C are in the appropriate range.

[0029] (Additives) The additive is preferably a cationic surfactant, an anionic surfactant, or an amphoteric surfactant. The cationic surfactant may be a surfactant having an amide group, a primary amine, a secondary amine, a tertiary amine, an imine, an enamine, or the like as a polar group. The anionic surfactant may be a surfactant having a carboxyl group, a sulfonic acid group, a sulfate ester group, a phosphate ester group, or the like as a polar group. Among them, it is preferable to include a cationic surfactant or an anionic surfactant as the additive.

[0030] The amine value of the cationic surfactant is preferably from 1 to 200 mgKOH / g, more preferably from 5 to 80 mgKOH / g, further preferably from 10 to 48 mgKOH / g, and particularly preferably from 35 to 48 mgKOH / g. In addition, the acid value of the anionic surfactant is preferably 1 to 200 mgKOH / g, more preferably 10 to 180 mgKOH / g, and even more preferably 50 to 150 mgKOH / g. It may be an amphoteric surfactant having the above amine value and acid value, or a cationic and anionic surfactant having the above amine value and acid value may be used in combination.

[0031] The proportion of the additive is preferably 5 to 100 parts by mass, more preferably 10 to 60 parts by mass, and even more preferably 20 to 40 parts by mass with respect to 100 parts by mass of the nanosilicon. When the addition amount of the additive is 5 parts by mass or more, aggregation of the nanosilicon can be suppressed and the viscosity of the slurry can be reduced, so that as a result, the cycle characteristics, charge-discharge capacity, and initial Coulomb efficiency in the battery can be improved. Also, if the addition amount of the additive is 60 parts by mass or less, the grinding time can be reduced and the production becomes easy.

[0032] The viscosity of the nanosilicon-containing slurry in the present invention is preferably 20 mPa·s or less, more preferably 0.5 to 10 mPa·s, and even more preferably 1.0 to 5 mPa·s. Also, the non-volatile content at 110°C is preferably 1 to 70% by mass, more preferably 8 to 40% by mass, and even more preferably 10 to 35% by mass.

[0033] [Active material for secondary battery] The active material for secondary battery of the present invention is not particularly limited as long as it contains the above-described nanosilicon of the present invention, but preferably contains a silicon-based inorganic compound together with the nanosilicon. The above-described nanosilicon of the present invention also has an action as an active material for secondary battery, but it can also be added to a known and commonly used active material for secondary battery and used. The active material for secondary battery of the present invention preferably has a structure in which the above nanosilicon is encapsulated in a matrix phase. Examples of the components constituting such a matrix phase include components derived from polysiloxane compounds and carbon source resins in the production methods described later, such as SiC (silicon carbide), SiOC (silicon oxycarbide), and SiOy (1 < y < 2).

[0034] The matrix phase preferably contains silicon, carbon and oxygen elements and has a three-dimensional network structure of a silicon-oxygen-carbon skeleton. This three-dimensional network structure of a silicon-oxygen-carbon skeleton has relatively high chemical stability, has a composite structure with carbon (carbonaceous phase), and exhibits small volumetric changes with respect to the absorption and release of lithium. The three-dimensional network structure of the matrix phase preferably contains a SiOC (silicon oxycarbide) structure. This three-dimensional network structure may contain a nitrogen element in addition to silicon, carbon and oxygen elements.

[0035] The secondary battery active material preferably has a carbon layer on its surface, that is, has a carbon coating on at least a part of its surface. The carbon layer (carbon coating) is preferably a coating made of low crystalline carbon. From the viewpoint of improving chemical stability and thermal stability, the amount of the carbon layer (carbon coating) is preferably 0.1% by mass to 30% by mass, more preferably 1% by mass to 25% by mass, and even more preferably 5% by mass to 20% by mass, based on 100% by mass of the secondary battery active material. The secondary battery composite active material may have a carbon layer (carbon coating) on ​​its surface continuously or intermittently. The carbon layer (carbon coating) is preferably formed on the surface of the active material by chemical vapor deposition.

[0036] The true density of the secondary battery active material is, for example, 1.6 g / cm 3 More than 2.6g / cm 3 The true density is set to 1.75 g / cm from the viewpoint of improving the energy density of the resulting secondary battery. 3 More than 1.80 g / cm is preferable. 3 The above is more preferable. The true density is a value measured using a true density measuring device.

[0037] If the average particle size of the active material for secondary batteries is too small, the specific surface area increases significantly, and when the active material is used as a secondary battery, the reversible charge / discharge capacity per unit volume may decrease due to an increase in the amount of SEI generated during charging and discharging. On the other hand, if the average particle size is too large, the adhesive strength with the current collector decreases, and the active material may peel off from the current collector. Therefore, the volume average particle size of the composite active material for secondary batteries is preferably 2 μm or more and 15 μm or less. The volume average particle size of the active material is more preferably 2.5 μm or more, and even more preferably 3.0 μm or more. The volume average particle size of the composite active material for secondary batteries is more preferably 12 μm or less, and even more preferably 10 μm or less.

[0038] The specific surface area of ​​the above secondary battery active material is 0.3 m 2 / g or more 10m 2 The specific surface area of ​​the active material for secondary batteries is preferably 0.5 m 2 / g or more is more preferable, and 1m 2 / g or more is particularly preferred. When the specific surface area is in the above range, the amount of solvent absorbed during electrode preparation can be appropriately maintained, and the amount of binder used to maintain binding properties can also be appropriately maintained. The specific surface area is a value determined by the BET method, and can be determined by nitrogen gas adsorption measurement, for example, using a specific surface area measurement device.

[0039] [Method for producing nanosilicon-containing slurry] The method for producing nanosilicon-containing slurry of the present invention is a method for producing nanosilicon-containing slurry by wet-pulverizing silicon raw material to obtain nanosilicon-containing slurry, in which beads of 0.5 mm or less are used for wet-pulverization, and the cumulative input power per unit weight of silicon raw material during wet-pulverization is 7500 kWh / t or more. Note that the above-mentioned nanosilicon-containing slurry of the present invention is not limited to the nanosilicon-containing slurry obtained by the method for producing the present invention.

[0040] The wet grinding is performed by adding beads to a slurry, which is a mixture of silicon raw material powder and a non-aqueous solvent, and stirring the mixture. The wet grinding is performed using a bead mill that is usually used for dispersion. In order to suppress oxidation of nanosilicon, the wet grinding is preferably performed in an inert gas atmosphere such as nitrogen or argon. The non-aqueous solvent is as described above, and ketone solvents such as MEK (methyl ether ketone) are preferable because they can suppress oxidation of the nanosilicon surface. The ratio of the non-aqueous solvent is, for example, 100 to 1000 parts by mass with respect to 100 parts by mass of nanosilicon. The additives described above may also be used in the wet grinding, and the ratio of the additives is, for example, 5 to 60 parts by mass with respect to 100 parts by mass of nanosilicon. The method of wet grinding is not particularly limited, and the silicon raw material and the additives may be added to the non-aqueous solvent, or the silicon raw material and the additives may be added to the non-aqueous solvent.

[0041] In the method for producing nanosilicon-containing slurry of the present invention, when the cumulative input power per weight during wet grinding is 7500 kWh / t or more, the contact force in the tangential direction changes from significant to significant in the normal direction with respect to nanosilicon. In addition, when nanosilicon is ground by the method for producing nanosilicon of the present invention, flat nanosilicon is produced, so the tangential force component of the force applied to the nanosilicon contributes to grinding, and efficient grinding is possible by performing grinding in a state where the tangential contact force is significant. On the other hand, when the normal contact force becomes significant, an extra collision force is required to satisfy the amount of the tangential force component required to grind nanosilicon, and the energy unnecessary for grinding nanosilicon contributes to other reactions (mechanochemical reactions) such as surface oxidation. Furthermore, the smaller the bead diameter, the larger the cumulative input power becomes, so by using beads with a bead diameter of 0.5 mm or less, the normal contact force becomes more likely to be significant. The bead diameter is preferably 0.4 mm or less, more preferably 0.3 mm or less, and particularly preferably 0.2 mm or less.

[0042] In reality, the smaller the bead diameter of the grinding media, the larger the cumulative input power at which the tangential contact force becomes significant, and the more the normal contact force becomes significant. For example, it is known that the tangential contact force is significant up to 5000 kWh / t for a bead diameter of 1.0 mm, 7000 kWh / t for 0.5 mm, and 9000 kWh / t for 0.2 mm. In order to achieve the target performance, it is necessary to use small beads of 0.5 mm or less when the cumulative input power is at least 10,000 kWh / t or more, but since the tangential contact force is as significant as possible while taking into account the balance with productivity, it is preferable to grind silicon using beads with a smaller bead diameter in terms of reducing silicon oxidation and improving charge / discharge characteristics.

[0043] In the method for producing nanosilicon-containing slurry of the present invention, wet pulverization is performed in two or more stages by changing the bead diameter, and it is preferable that the ratio (D1 / D2) of the initial bead diameter D1 and the bead diameter D2 of the second or subsequent stages is 1.5 or more. By performing multi-stage pulverization in which the bead diameter is changed based on the cumulative input power, it is possible to produce a nanosilicon-containing slurry containing nanosilicon with reduced mechanochemical reactions including surface oxidation. Although pulverization with a single stage using a small bead diameter is possible with reduced mechanochemical reactions, the productivity is not favorable, and depending on the particle size of the raw material, clogging may occur in the bead mill, making operation difficult. If the productivity is significantly reduced, silicon may be oxidized due to oxygen or moisture mixed into the system due to incomplete sealing, or a reaction with the solvent used for pulverization. Therefore, it is preferable to pulverize silicon in as short a time as possible by multi-stage pulverization.

[0044] The silicon raw material preferably has a silicon purity of 97% or more, more preferably 99% or more. The specific surface area of ​​the silicon raw material is preferably small in order to suppress oxidation, and is preferably 30 m 2 / g or less, more preferably 25m 2 / g or less, particularly preferably 20m 2 / g or less. The volume average particle size of the silicon raw material is, for example, 0.1 to 10 μm, and preferably 0.5 to 8 μm. As the silicon raw material, commercially available silicon powder can be used.

[0045] The wet milling is preferably performed with a bead mill integrated input power per unit amount of silicon raw material within the range of 7500 kWh / t to 45000 kWh / t, more preferably 8000 kWh / t to 35000 kWh / t. By setting the bead mill integrated input power within the above range, the contact force in the normal direction, rather than the tangential direction, can be made significant in the wet milling of nanosilicon.

[0046] In the above wet grinding, the true density of the beads is preferably small in order to reduce the cumulative input power, and is preferably 6.5 g / cm 3 Less than 6.3 g / cm, more preferably 6.3 g / cm 3 The volumetric filling rate of the beads in the bead mill in wet grinding should be in a moderate range from the viewpoint of reducing the cumulative input power, preferably 50 to 95%, more preferably 60 to 90%. The peripheral speed of the bead mill should be low from the viewpoint of reducing the cumulative input power, preferably less than 20 m / s, more preferably less than 15 m / s.

[0047] Furthermore, when wet grinding is performed in multiple stages with different bead diameters, the bead diameter from the second (second stage) onwards is preferably 0.2 mm or less, more preferably 0.1 mm or less, and particularly preferably 0.05 mm or less. The true density of the beads from the second (second stage) onwards is preferably 6.5 g / cm 3 Less than 6.3 g / cm, more preferably 6.3 g / cm 3 The volumetric filling rate of the beads is preferably 50 to 95%, more preferably 60 to 90%. The peripheral speed of the beads mill is preferably less than 20 m / s, more preferably less than 15 m / s.

[0048] [Method of manufacturing active material for secondary batteries] The method for producing an active material for secondary batteries of the present invention is a method for obtaining an active material for secondary batteries by drying a mixture of nanosilicon obtained by the above-mentioned method for producing a nanosilicon-containing slurry and a resin, etc., and firing the mixture under an inert gas atmosphere. The resin constitutes the above-mentioned matrix phase, and is preferably composed of a polysiloxane compound and a carbon source resin. Therefore, the mixing of the obtained nanosilicon and the resin, etc., and the drying of the obtained mixture are, in detail, performed by mixing and dispersing the obtained nanosilicon, the polysiloxane compound, and the carbon source resin, and drying the obtained mixture.

[0049] The polysiloxane compound is not particularly limited as long as it is a resin containing at least one of polycarbosilane, polysilazane, polysilane, and polysiloxane structures. It may be a single resin, or a composite resin having this as a segment and chemically bonded with other polymer segments. The form of the composite may be a copolymer such as graft, block, random, or alternating. For example, there is a composite resin having a graft structure in which a polysiloxane segment is chemically bonded to the side chain of a polymer segment, and a composite resin having a block structure in which a polysiloxane segment is chemically bonded to the end of a polymer segment.

[0050] The polysiloxane segment preferably has a structural unit represented by the following general formula (S-1) and / or the following general formula (S-2).

[0051] [ka]

[0052] [ka]

[0053] (In the above general formulas (S-1) and (S-2), R 1 represents an aromatic hydrocarbon substituent or an alkyl group. 2 and R 3respectively represent an alkyl group, a cycloalkyl group, an aryl group, or an aralkyl group.

[0054] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, a 1-ethyl-1-methylpropyl group, etc. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, etc.

[0055] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.

[0056] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.

[0057] Examples of polymer segments other than the polysiloxane segment contained in the polysiloxane compound include vinyl polymer segments such as acrylic polymers, fluoroolefin polymers, vinyl ester polymers, aromatic vinyl polymers, and polyolefin polymers, as well as polymer segments such as polyurethane polymer segments, polyester polymer segments, and polyether polymer segments. Among these, vinyl polymer segments are preferred.

[0058] The polysiloxane compound may be a composite resin in which a polysiloxane segment and a polymer segment are bonded together in a structure represented by the following structural formula (S-3), or may have a three-dimensional network polysiloxane structure.

[0059] [ka]

[0060] (In the formula, the carbon atom is a carbon atom constituting a polymer segment, and the two silicon atoms are silicon atoms constituting a polysiloxane segment.)

[0061] The polysiloxane segment of the polysiloxane compound may have a functional group capable of reacting by heating, such as a polymerizable double bond, in the polysiloxane segment. By subjecting the polysiloxane compound to heat treatment before thermal decomposition, a crosslinking reaction proceeds and the compound becomes solid, which makes it easy to carry out the thermal decomposition treatment.

[0062] Examples of the polymerizable double bond include a vinyl group and a (meth)acryloyl group. The number of polymerizable double bonds in the polysiloxane segment is preferably 2 or more, more preferably 3 to 200, and even more preferably 3 to 50. In addition, by using a composite resin having 2 or more polymerizable double bonds as the polysiloxane compound, the crosslinking reaction can be easily promoted.

[0063] The polysiloxane segment may have a silanol group and / or a hydrolyzable silyl group. Examples of the hydrolyzable group in the hydrolyzable silyl group include a halogen atom, an alkoxy group, a substituted alkoxy group, an acyloxy group, a phenoxy group, a mercapto group, an amino group, an amide group, an aminooxy group, an iminoxy group, and an alkenyloxy group, and the hydrolyzable silyl group becomes a silanol group by hydrolysis of these groups. In parallel with the thermosetting reaction, a hydrolysis condensation reaction proceeds between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, thereby obtaining a solid polysiloxane compound.

[0064] The silanol group in the present invention is a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. The hydrolyzable silyl group in the present invention is a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and specifically includes, for example, a group represented by the following general formula (S-4).

[0065] [ka]

[0066] (In the formula, R 4 R represents a monovalent organic group such as an alkyl group, an aryl group, or an aralkyl group. 5 is a halogen atom, an alkoxy group, an acyloxy group, an allyloxy group, a mercapto group, an amino group, an amido group, an aminooxy group, an iminoxy group, or an alkenyloxy group, and b is an integer of 0 to 2.

[0067] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group.

[0068] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group.

[0069] Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.

[0070] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0071] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a sec-butoxy group, and a tert-butoxy group.

[0072] Examples of the acyloxy group include formyloxy, acetoxy, propanoyloxy, butanoyloxy, pivaloyloxy, pentanoyloxy, phenylacetoxy, acetoacetoxy, benzoyloxy, and naphthoyloxy.

[0073] The allyloxy group includes, for example, phenyloxy, naphthyloxy, and the like.

[0074] Examples of the alkenyloxy group include a vinyloxy group, an allyloxy group, a 1-propenyloxy group, an isopropenyloxy group, a 2-butenyloxy group, a 3-butenyloxy group, a 2-pentenyloxy group, a 3-methyl-3-butenyloxy group, and a 2-hexenyloxy group.

[0075] Examples of the polysiloxane segment having the structural unit represented by the above general formula (S-1) and / or the above general formula (S-2) include those having the following structures.

[0076] [ka]

[0077] [ka]

[0078] [ka]

[0079] R in the above structural formulas (1) to (3) 6 is the above R 1 In addition, R in the above structural formulas (4) to (8) has the same meaning as 7 and R 8 are the above R 2 and R 3 It has the same meaning as:

[0080] The polymer segment may have various functional groups as necessary within the scope of not impairing the effects of the present invention. Examples of such functional groups include a carboxyl group, a blocked carboxyl group, a carboxylic anhydride group, a tertiary amino group, a hydroxyl group, a blocked hydroxyl group, a cyclocarbonate group, an epoxy group, a carbonyl group, a primary amide group, a secondary amide group, a carbamate group, and a functional group represented by the following structural formula (S-5).

[0081] [ka]

[0082] The polymer segment may also have a polymerizable double bond such as a vinyl group or a (meth)acryloyl group.

[0083] The polysiloxane compound of the present invention can be produced by known methods, and is preferably produced by the following methods (1) to (3), although the method is not limited thereto.

[0084] (1) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment, and this polymer segment is mixed with a silane compound containing a silanol group and / or a hydrolyzable silyl group, and a silane compound having both a polymerizable double bond, to carry out a hydrolysis condensation reaction.

[0085] (2) A method in which a polymer segment containing a silanol group and / or a hydrolyzable silyl group is prepared in advance as a raw material for the polymer segment. A polysiloxane is also prepared in advance by subjecting a silane compound containing a silanol group and / or a hydrolyzable silyl group, and a silane compound having both a polymerizable double bond, to a hydrolysis condensation reaction. The polymer segment and the polysiloxane are then mixed together to carry out a hydrolysis condensation reaction.

[0086] (3) A method in which the above polymer segment, a silane compound containing a silane compound having both a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond, and a polysiloxane are mixed together to carry out a hydrolysis condensation reaction.

[0087] The carbon source resin is not particularly limited as long as it has good miscibility with the polysiloxane compound and can be carbonized by high-temperature firing in an inert atmosphere. It is preferable to use synthetic resins having aromatic functional groups or natural chemical raw materials, and it is more preferable to use phenolic resins from the viewpoints of cheap availability and removal of impurities.

[0088] Examples of synthetic resins include thermoplastic resins such as polyvinyl alcohol and polyacrylic acid, and thermosetting resins such as phenol resin and furan resin. Examples of natural chemical raw materials include heavy oils, particularly tar pitches, such as coal tar, light tar oil, medium tar oil, heavy tar oil, naphthalene oil, anthracene oil, coal tar pitch, pitch oil, mesophase pitch, oxygen-crosslinked petroleum pitch, and heavy oil.

[0089] In the above mixing, although there is no particular limitation, a device having a general-purpose dispersing and mixing function can be used. Among them, examples include a stirrer, an ultrasonic mixer, a premix disperser, etc. In the desolvation and drying operation for distilling off the organic solvent, a dryer, a reduced pressure dryer, a spray dryer, etc. can be used.

[0090] It is preferable to set the amount of nanosilicon obtained by the above-mentioned method for producing a nanosilicon-containing slurry to 3 to 50 mass%, the solid content of the polysiloxane compound to 15 to 85 mass%, and the solid content of the carbon source resin to 3 to 70 mass%, relative to the weight of the dried material, and it is more preferable to set the solid content of the silicon particles to 8 to 40 mass%, the solid content of the polysiloxane compound to 20 to 70 mass%, and the solid content of the carbon source resin to 3 to 60 mass%.

[0091] By calcining the above-mentioned dried material under an inert atmosphere, the thermally decomposable organic components are completely decomposed, and by precisely controlling the calcination conditions for the other main components, a calcined material suitable for use as an active material for secondary batteries can be obtained.

[0092] The above-mentioned firing is performed according to a predetermined program, and the maximum temperature is the maximum temperature that is set and strongly affects the structure and performance of the fired product. The maximum temperature is preferably 1020°C to 1180°C, and more preferably 1070°C to 1150°C. By firing within this temperature range, the microstructure of the material that retains the above-mentioned chemical bond state of silicon and carbon can be improved, and silicon oxidation due to excessively high temperature firing can be avoided, resulting in better charge and discharge characteristics.

[0093] The calcination method is not particularly limited, but a reaction device having a heating function in the atmosphere may be used, and treatment may be performed by a continuous method or a batch method. The calcination device may be appropriately selected from a fluidized bed reactor, a rotary furnace, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a rotary kiln, etc. according to the purpose. The inert atmosphere is not particularly limited, but it is sufficient that it does not contain an oxidizing gas, and nitrogen, argon, etc. may be used.

[0094] In addition, an oxidation treatment may be performed before the above-mentioned firing. This oxidation treatment can provide a thin oxide film on the surface of the silicon. When used in a battery, it is possible to prevent the silicon surface from being exposed to the electrolyte, and there is an effect of suppressing decomposition of the electrolyte, thereby improving the cycle characteristics of the active material. The oxidation treatment conditions are preferably in the air at a temperature range of 200°C to 440°C, more preferably 300°C to 420°C.

[0095] The above-mentioned fired product is pulverized and classified as necessary to obtain an active material for secondary batteries. The pulverization may be performed in one step until the particle size reaches the desired particle size, or may be performed in several steps. For example, if the fired product is in the form of lumps or agglomerated particles of 10 mm or more, and an active material of 10 μm is to be produced, the material is coarsely pulverized with a jaw crusher, roll crusher, etc. to particles of about 1 mm, then pulverized to 100 μm with a glow mill, ball mill, etc., and pulverized to 10 μm with a bead mill, jet mill, etc. The particles produced by pulverization may contain coarse particles, and classification is performed to remove these particles and to remove fine powder and adjust the particle size distribution. The classifier used may be a wind classifier, a wet classifier, etc., depending on the purpose, but when removing coarse particles, a classification method that passes through a sieve is preferable because it can reliably achieve the purpose.

[0096] [Negative electrode] The negative electrode of the present invention includes the active material for secondary batteries of the present invention. The negative electrode is obtained by applying a slurry composed of the active material for secondary batteries of the present invention and an organic binder as essential components, and optionally other components such as a conductive assistant, onto a copper foil collector to form a thin film. The active material for secondary batteries contains the nanosilicon of the present invention, and therefore exhibits good charge / discharge characteristics when used as a negative electrode.

[0097] A negative electrode can also be prepared by adding a known and commonly used carbon material such as graphite to the above slurry. Examples of the carbon material such as graphite include natural graphite, artificial graphite, hard carbon, and soft carbon.

[0098] The negative electrode can be obtained, for example, by kneading the above-mentioned negative electrode active material for secondary batteries and a binder, which is an organic binding material, together with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, or a pressure kneader to prepare a negative electrode material slurry, which is then applied to a current collector to form a negative electrode layer. Alternatively, the negative electrode can be obtained by forming the paste-like negative electrode material slurry into a shape such as a sheet or pellet, and integrating it with a current collector.

[0099] The organic binder is not particularly limited, but examples thereof include styrene-butadiene rubber copolymers (SBR); (meth)acrylic copolymers consisting of ethylenically unsaturated carboxylic acid esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, etc.) and ethylenically unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, etc.); and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (CMC). Aqueous binders with high chemical stability can also be used as the organic binder.

[0100] Depending on their respective physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), etc. The content of the organic binder in the negative electrode layer of the lithium ion secondary battery negative electrode is preferably 1 to 30 mass%, more preferably 2 to 20 mass%, and even more preferably 3 to 15 mass%.

[0101] An organic binder content of 1% by mass or more provides good adhesion and prevents the negative electrode structure from being damaged by expansion and contraction during charging and discharging. On the other hand, an organic binder content of 30% by mass or less prevents an increase in electrode resistance.

[0102] In addition, the negative electrode material slurry may be mixed with a conductive assistant as necessary. Examples of the conductive assistant include carbon black, graphite, acetylene black, and oxides and nitrides that exhibit conductivity. The amount of the conductive assistant used may be about 1 to 15% by mass with respect to the negative electrode active material of the present invention.

[0103] The material and shape of the current collector are not particularly limited, and may be a strip of copper, nickel, titanium, stainless steel, or the like in the form of foil, perforated foil, mesh, etc. Porous materials such as porous metal (foamed metal) and carbon paper may also be used.

[0104] The method for applying the negative electrode material slurry to the current collector is not particularly limited, and examples thereof include known methods such as metal mask printing, electrostatic painting, dip coating, spray coating, roll coating, doctor blade, gravure coating, screen printing, etc. After application, it is preferable to perform a rolling treatment using a flat plate press, a calendar roll, etc. as necessary.

[0105] The negative electrode material slurry formed into a sheet, pellet or other shape can be integrated with the current collector by a known method, such as rolling, pressing, or a combination of these.

[0106] The negative electrode layer formed on the current collector and the negative electrode layer integrated with the current collector are preferably heat-treated according to the organic binder used. For example, when a known and commonly used water-based styrene-butadiene rubber copolymer (SBR) is used, the heat treatment may be performed at 100 to 130°C, and when an organic binder having a polyimide or polyamideimide as the main skeleton is used, the heat treatment is preferably performed at 150 to 450°C.

[0107] This heat treatment removes the solvent, hardens the binder, and increases the strength, improving the adhesion between the particles and between the particles and the current collector. It is preferable to carry out these heat treatments in an inert atmosphere such as helium, argon, or nitrogen, or in a vacuum atmosphere, in order to prevent oxidation of the current collector during the treatment.

[0108] In addition, it is preferable to press the negative electrode after the heat treatment. In the negative electrode for secondary batteries using the negative electrode active material of the present invention, the electrode density is 1.0 to 1.8 g / cm 3 and preferably 1.1 to 1.7 g / cm 3 More preferably, it is 1.2 to 1.6 g / cm 3 Regarding the electrode density, the higher the density, the more the adhesion and the volumetric capacity density of the electrode tend to improve, but if the density is too high, the voids in the electrode are reduced, weakening the effect of suppressing the volume expansion of silicon and the like, and thus deteriorating the cycle characteristics.

[0109] [Secondary battery] When the secondary battery of the present invention is used as a wet electrolyte secondary battery, for example, the secondary battery of the present invention can be constructed by disposing a positive electrode and a negative electrode of the present invention opposite each other with a separator interposed therebetween and injecting an electrolyte solution into the negative electrode. The secondary battery of the present invention can be manufactured by assembling the secondary battery according to this configuration.

[0110] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. In this case, the current collector can be a strip of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.

[0111] The positive electrode material used in the positive electrode layer is not particularly limited. When preparing a lithium ion secondary battery among non-aqueous electrolyte secondary batteries, for example, a metal compound, a metal oxide, a metal sulfide, or a conductive polymer material capable of doping or intercalating lithium ions may be used, and is not particularly limited. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. can be used alone or in combination.

[0112] The separator may be, for example, a nonwoven fabric, a cloth, a microporous film, or a combination thereof, mainly composed of a polyolefin such as polyethylene or polypropylene. If the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery are not in direct contact with each other, it is not necessary to use a separator.

[0113] As the electrolyte, for example, a so-called organic electrolyte can be used in which a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, or LiSO3CF3 is dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, or ethyl acetate, or a mixture of two or more components.

[0114] The structure of the secondary battery of the present invention is not particularly limited, but typically, a positive electrode, a negative electrode, and a separator that is provided as necessary are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in a flat plate shape to form a stacked electrode plate group, and the electrode plate group is enclosed in an exterior body.

[0115] The secondary battery of the present invention is not particularly limited, and may be used as a paper-type battery, a button-type battery, a coin-type battery, a laminated battery, a cylindrical battery, a square battery, etc. The above-mentioned lithium ion secondary battery negative electrode active material of the present invention can also be applied to electrochemical devices in general that use insertion and desorption of lithium ions as a charge / discharge mechanism, such as hybrid capacitors and solid lithium secondary batteries. EXAMPLES

[0116] A polysiloxane compound was prepared by the method of Synthesis Example 1 below, and a curable resin composition was prepared by the method of Synthesis Example 2. Nanosilicon was prepared by the methods of Examples 1 to 18 and Comparative Examples 1 to 4, and the curable resin composition thus prepared was used to prepare an active material for a secondary battery. After that, a half-cell battery was prepared from the active material for a secondary battery, and the battery characteristics were evaluated.

[0117] Synthesis Example 1: Preparation of polysiloxane compound A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 1,421 parts by mass of methyltrimethoxysilane (hereinafter, referred to as "MTMS") and heated to 60° C. Next, a mixture of 0.17 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 207 parts by mass of deionized water was dropped into the reaction vessel over a period of 5 minutes, and the mixture was stirred at a temperature of 80° C. for 4 hours to carry out a hydrolysis and condensation reaction of MTMS. The condensate obtained by the hydrolysis and condensation reaction was distilled at a temperature of 40 to 60°C and under a reduced pressure of 40 to 1.3 kPa. The phrase "under a reduced pressure of 40 to 1.3 kPa" means that the reduced pressure condition at the start of methanol distillation is 40 kPa, and the pressure is finally reduced to 1.3 kPa. The same applies to the following description. By removing the methanol and water produced during the reaction, 1,000 parts by mass of a liquid containing a condensate of MTMS having a number average molecular weight of 1,000 to 5,000 (hereinafter also referred to as "a1"). The content of the active ingredient in the obtained liquid was 70% by mass. The effective ingredient is calculated by dividing the theoretical yield (parts by mass) when all methoxy groups of a silane monomer such as MTMS undergo a condensation reaction by the actual yield (parts by mass) after the condensation reaction, i.e., [theoretical yield (parts by mass) when all methoxy groups of a silane monomer undergo a condensation reaction / actual yield (parts by mass) after the condensation reaction].

[0118] Synthesis Example 2: Production of curable resin composition A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 150 parts by mass of butanol (hereinafter also referred to as "BuOH"), 105 parts by mass of phenyltrimethoxysilane (hereinafter also referred to as "PTMS"), and 277 parts by mass of dimethyldimethoxysilane (hereinafter also referred to as "DMDMS"), and the temperature was raised to 80°C. Next, at the same temperature, a mixture containing 21 parts by mass of methyl methacrylate (hereinafter also referred to as "MMA"), 4 parts by mass of butyl methacrylate (hereinafter also referred to as "BMA"), 3 parts by mass of butyric acid (hereinafter also referred to as "BA"), 2 parts by mass of methacryloyloxypropyltrimethoxysilane (hereinafter also referred to as "MPTS"), 3 parts by mass of BuOH, and 0.6 parts by mass of butylperoxy-2-ethylhexanoate (hereinafter also referred to as "TBPEH") was dropped into the reaction vessel over 6 hours. After the dropwise addition was completed, the mixture was further reacted at the same temperature for 20 hours to obtain an organic solvent solution of a vinyl polymer (a2) having a number average molecular weight of 10,000 and having a hydrolyzable silyl group. Next, a mixture of 0.04 parts by mass of isopropyl acid phosphate ("Phoslex A-3" manufactured by SC Organic Chemical Co., Ltd.) and 112 parts by mass of deionized water was added dropwise over a period of 5 minutes, and the mixture was stirred at the same temperature for a further 10 hours to cause a hydrolysis condensation reaction, thereby obtaining a liquid containing a composite resin in which the hydrolyzable silyl group of the vinyl polymer (a2) and the hydrolyzable silyl group and silanol group of the polysiloxane derived from the PTMS and DMDMS were bonded together. Next, 472 parts by mass of the MTMS condensate (a1) obtained in Synthesis Example 1 and 80 parts by mass of deionized water were added to this liquid, and the mixture was stirred at the same temperature for 10 hours to cause a hydrolysis condensation reaction, and the produced methanol and water were removed by distillation under the same conditions as in Synthesis Example 1. Next, 250 parts by mass of BuOH was added to obtain 1,000 parts by mass of a curable resin composition with a non-volatile content of 60.1% by mass.

[0119] [Evaluation method] · 29 Si-NMR The sample was collected in a φ4 mm solid-state NMR sample tube and subjected to single pulse measurement using a solid-state NMR analyzer (JNM-ECA600, manufactured by JEOL RESONACE). The solid-state NMR spectrum data obtained was Fourier transformed using Delta5, and waveform separation was performed using the Gauss+Lorentz function in ACD Labs software. The peak area ratios [(ii) / (i) ratio, (iv) / (iii) ratio] were calculated based on the peak areas of the peaks in each chemical shift value (ppm) range obtained by waveform separation.

[0120] HR-TEM The thickness of the silicon oxide film was confirmed using a HR-TEM (JEM-ARMF300, manufactured by JEOL Ltd.).

[0121] XRD The measurements were performed using an X-ray crystal structure analyzer (Cu-Kα) (New D8 ADVANCE manufactured by Bruker AXS). The crystallite size was calculated based on the full width at half maximum (FWHM) by the Scherrer method described below. L = Kλ / (βcosθ) K: shape factor, λ: X-ray wavelength, β: peak half-width (in radians), θ: Bragg angle, L: crystallite diameter

[0122] ·Specific surface area The specific surface area was measured by nitrogen adsorption measurement using a specific surface area measuring device (BELSORP-mini, manufactured by BELJAPAN).

[0123] Battery characteristic evaluation Battery characteristics were measured using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation), and the charge / discharge characteristics were evaluated under the following conditions: room temperature 25°C, cutoff voltage range 0.005-1.5V, charge / discharge rate 0.1C (1-3 times) and 0.2C (after 4 cycles), constant current / constant voltage charge / constant current discharge. When switching between charge and discharge, the battery was left in an open circuit for 30 minutes. The initial coulombic efficiency (initial efficiency) was calculated as follows: Initial coulombic efficiency (%) = initial discharge capacity (mAh / g) / initial charge capacity (mAh / g)

[0124] Example 1 (1st stage silicon crushing) 5000g of silicon powder (manufactured by Kojundo Kagaku) ​​with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and stirred well. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-milled for 2 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a nanosilicon-containing slurry 1-1 in which nanosilicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the true density of the beads was 6.0 g / cm 3 The peripheral speed of the bead mill was set to 12 m / s.

[0125] (Second stage silicon crushing) 20,000 g of this nanosilicon-containing slurry 1 was placed in a stirring tank and thoroughly stirred. The stirring tank was covered and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 4.5 hours using a bead mill (MSC Mill MSC220, manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain nanosilicon-containing slurry 1-2 in which nanosilicon was uniformly dispersed in the dispersion medium. The orientation degree f(111) of the (111) plane of the nanosilicon contained in the nanosilicon-containing slurry 1-2 was 0.35. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the true density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 14 m / s. The obtained nanosilicon-containing slurry 1-2 was dried at room temperature under vacuum for 10 hours to obtain a nanosilicon dried material 1. 29Si-NMR measurements were performed, and the ratio (i) of the area of ​​the peak in the range of -75 to -85 ppm, which indicates Si-Si bonds, to the area (ii) of other peaks including at least SiO4, SiO3C, SiO2C2, SiOC3, SiC4, etc. [(i) / (ii) ratio] was 0.63. Six drops of nanosilicon-containing slurry 1-2 were placed on a glass for XRD measurement, and dried by spinning at 2000 rpm for 10 seconds on a spin coater to obtain a nanosilicon coating. Crystal structure analysis was performed using this sample using X-ray diffraction. The degree of orientation f(111) of the silicon (111) plane based on the Lotgering method was 0.35. The nanosilicon dried material 1 29 The Si-NMR spectrum is shown in Figure 1, and the crystal structure analysis (XRD) using ray diffraction is shown in Figure 2.

[0126] The nanosilicon-containing slurry 1-2, the curable resin composition of Synthesis Example 2 (hereinafter also referred to as SiOC), and a phenolic resin (manufactured by Sumitomo Bakelite, SUMILITE RESIN PR-53570: hereinafter also referred to as C) were mixed so that the composition after firing was SiOC / C / Si=10 / 40 / 50, and charged into a three-necked separable flask. One neck of the three-necked separable flask was covered, and a nitrogen inlet tube and a solvent trap device were connected to the remaining two necks. Nitrogen was introduced into the flask, and while stirring the mixture with a magnetic stirrer, the flask was heated to 120°C in an oil bath, and the solvent was distilled off until the stirrer stopped moving. After that, it was cooled to room temperature, and a dried resin product, which is a firing precursor, was obtained. Then, the dried resin product, which is a firing precursor, was fired in a nitrogen atmosphere at a temperature of 1050°C for 6 hours, and a black solid product was obtained. The obtained black solid product was pulverized with a planetary ball mill to obtain a negative electrode active material powder.

[0127] A mixed slurry containing 80% by mass of the above-mentioned negative electrode active material powder, 10% by mass of acetylene black as a conductive assistant, and 10% by mass of a mixture of CMC and SBR as a binder was prepared and formed on a copper foil. It was then dried under reduced pressure at 110°C and a Li metal foil was used as the counter electrode to prepare a half cell. The battery characteristics of this half cell were evaluated. The measurement results of the charge and discharge characteristics showed that the initial discharge capacity was 1430mAh / g and the initial efficiency was 83.2%.

[0128] For the evaluation of battery characteristics (full cell), a positive electrode film was prepared using a single-layer sheet of LiCoO2 as the positive electrode active material and aluminum foil as the current collector, and a negative electrode film was prepared by mixing graphite powder and active material powder with a discharge capacity design value of 450mAh / g. A non-aqueous electrolyte solution was used in which lithium hexafluorophosphate was dissolved at a concentration of 1mol / L in a 1 / 1 volumetric mixture of ethylene carbonate (hereinafter also referred to as "EC") and diethyl carbonate (hereinafter also referred to as "DEC"), and a laminated lithium ion secondary battery was prepared using a 30μm thick polyethylene microporous film as a separator. The laminated lithium ion secondary battery was charged at a constant current of 1.2mA (0.25c based on the positive electrode) at 25℃ until the voltage of the test cell reached 4.2V, and after reaching 4.2V, the current was reduced to keep the cell voltage at 4.2V, and the discharge capacity was calculated. The capacity retention rate after 300 cycles was 84%, with one cycle being charge and discharge within a voltage range of 2.5V to 4.2V. After charge and discharge, the laminate cell was disassembled in a glove box in an argon atmosphere, the negative electrode was removed, washed with an EC / DEC mixed solution, and then left to dry. The maximum thickness of the oxide film in the electrode film was measured by HR-TEM. The rate of change in the thickness of the negative electrode film before and after charge and discharge was taken as the negative electrode expansion rate. The negative electrode expansion rate was 19%. The results are shown in Table 1. The HR-TEM observation image in Example 1 is shown in Figure 3.

[0129] Example 2 (1st stage silicon crushing) 100 g of commercially available silicon powder (manufactured by Kojundo Kagaku) ​​with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 40 g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 400 g of MEK were mixed in a stirring tank and stirred well. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-pulverized for 2 hours using a bead mill (Ultra Apec Mill UAM-015 manufactured by Hiroshima Metal & Machinery Co., Ltd.) to obtain a nanosilicon-containing slurry 2 in which nanosilicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 12 m / s. The nanosilicon-containing slurry 2 was dried in a vacuum at room temperature for 10 hours or more to obtain a nanosilicon dried product 2. This nanosilicon dried product 2 was fired at 500 ° C. in a nitrogen atmosphere for 1 hour to obtain a nanosilicon fired product 2. The oxygen concentration of the nanosilicon sintered product 1 was measured and found to be 8.3 wt%. The specific surface area was 210 m 2 The value obtained by dividing the oxygen concentration of the fired nanosilicon material 2 by the specific surface area of ​​the fired nanosilicon material 2 was 0.04.

[0130] The nanosilicon-containing slurry 2, the curable resin composition of Synthesis Example 1, and a phenolic resin (Sumitomo Bakelite, SUMILITE RESIN PR-53570) were mixed so that the SiOC / C / Si ratio was 10 / 40 / 50, calculated based on the composition after firing, and charged into a three-necked separable flask. One neck was covered, and a nitrogen inlet tube and a solvent trap were connected to the remaining two necks. Nitrogen was introduced into the flask, and the flask was heated to 120°C in an oil bath while stirring the mixture with a magnetic stirrer, and the solvent was distilled off until the stirrer stopped moving. After that, the mixture was cooled to room temperature to obtain a dried resin product, which is a firing precursor. After that, the dried resin product, which is a firing precursor, was fired in a nitrogen atmosphere at a temperature of 1050°C for 6 hours to obtain a black solid product. The obtained black solid product was pulverized with a planetary ball mill to obtain a negative electrode active material powder.

[0131] A mixed slurry containing 80% by mass of the negative electrode active material powder, 10% by mass of acetylene black as a conductive assistant, and 10% by mass of a mixture of CMC and SBR as a binder was prepared and formed on a copper foil. It was then dried under reduced pressure at 110°C and a Li metal foil was used as the counter electrode to prepare a half cell. The charge and discharge characteristics of this half cell were evaluated using a two-phase battery charge and discharge measuring device (manufactured by Hokuto Co., Ltd.) with a cutoff voltage range of 0.005 to 1.5 V. The measurement results of the charge and discharge characteristics showed that the initial discharge capacity was 1450 mAh / g and the initial efficiency was 82.0%.

[0132] For the evaluation of battery characteristics (full cell), a positive electrode film was prepared using a single-layer sheet of LiCoO2 as the positive electrode active material and aluminum foil as the current collector, and a negative electrode film was prepared by mixing graphite powder and active material powder with a discharge capacity design value of 450mAh / g. A non-aqueous electrolyte solution was used in which lithium hexafluorophosphate was dissolved at a concentration of 1mol / L in a 1 / 1 volumetric mixture of ethylene carbonate (hereinafter also referred to as "EC") and diethyl carbonate (hereinafter also referred to as "DEC"), and a laminated lithium ion secondary battery was prepared using a 30μm thick polyethylene microporous film as a separator. The laminated lithium ion secondary battery was charged at a constant current of 1.2mA (0.25c based on the positive electrode) at 25℃ until the voltage of the test cell reached 4.2V, and after reaching 4.2V, the current was reduced to keep the cell voltage at 4.2V, and the discharge capacity was calculated. Charging and discharging within a voltage range of 2.5V to 4.2V constitutes one cycle, and the capacity retention rate after 300 cycles was 82%. After charging and discharging, the laminated cell was disassembled in a glove box in an argon atmosphere, and the negative electrode was removed and washed with an EC / DEC mixture, then left to dry, and the maximum thickness of the oxide film on the electrode was measured using HR-TEM. The rate of change in the thickness of the negative electrode film before and after charging and discharging was taken as the negative electrode expansion rate. The negative electrode expansion rate was 19%. The results are shown in Tables 2 and 3.

[0133] Example 3 Wet milling was performed in the same manner as in Example 2, except that the bead diameter during wet milling with the bead mill was 0.03 mm and the milling time was 12 hours, to prepare nanosilicon-containing slurry 3. A negative electrode active material was prepared using this nanosilicon-containing slurry 3. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 2. The results are shown in Tables 2 and 3.

[0134] Example 4 (1st stage silicon crushing) A nanosilicon-containing slurry 1-1 was prepared in the same manner as in Example 1. (Second stage silicon crushing) 300 g of the nanosilicon-containing slurry 1-1 was placed in a stirring tank and thoroughly stirred. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere inside the tank. This solution was wet-milled for 4 hours using a bead mill (Ultra Apec Mill UAM-015, manufactured by Hiroshima Metal & Machinery Co., Ltd.) to obtain nanosilicon-containing slurry 4 in which nanosilicon was uniformly dispersed in the dispersion medium. At this time, the diameter of the beads used in the bead mill was 0.1 mm, and the density of the beads was 6.0 g / cm. 3 The bead filling rate was 70%, and the peripheral speed of the bead mill was 12 m / s. The nanosilicon-containing slurry 4, the curable resin composition of Synthesis Example 1, and a phenolic resin (Sumitomo Bakelite, SUMILITE RESIN PR-53570) were mixed to a SiOC / C / Si ratio of 10 / 40 / 50 calculated based on the composition after firing, and charged into a three-necked separable flask. The remaining operations were performed in the same manner as in Example 1 to obtain a negative electrode active material powder. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0135] Examples 5-8 A nanosilicon-containing slurry 5-8 was produced by wet grinding silicon in the same manner as in Example 4, except that the bead diameter and grinding time in the first stage and the bead diameter and grinding time in the second stage were changed as shown in Table 2. A negative electrode active material was produced using this nanosilicon-containing slurry 5-8. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0136] Example 9 A nanosilicon-containing slurry 9 was prepared by wet grinding using a bead mill in the same manner as in Example 2, except that the specific surface area of ​​the silicon raw material was changed as shown in Table 2. A negative electrode active material was prepared using this nanosilicon-containing slurry 9. Using this, a half cell was evaluated in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0137] Examples 10-11 Wet milling with a bead mill was carried out in the same manner as in Example 2, except that the density of the beads during wet milling with a bead mill and the milling time were changed as shown in Table 2, to produce nanosilicon-containing slurry 10-11. A negative electrode active material was produced using this nanosilicon-containing slurry 10-11. Using this, a half cell was evaluated in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0138] Examples 12-13 Wet milling was performed in the same manner as in Example 2, except that the bead filling rate during wet milling in the bead mill and the milling time were changed as shown in Table 2, to prepare nanosilicon-containing slurry 12-13. A negative electrode active material was prepared using this nanosilicon-containing slurry 12-13. Using this, a half cell was evaluated in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0139] Example 14 (1st stage silicon crushing) 5000g of commercially available silicon powder (manufactured by Kojundo Kagaku) ​​with a silicon purity of 99.9% by mass and a volume average particle size of 3.2 μm, 2000g of DISPERBYK9077 (manufactured by BYK Additives & Instruments, DISPERBYK is a registered trademark), and 20000g of methyl ethyl ketone (hereinafter also referred to as "MEK") were mixed in a stirring tank and stirred well. The stirring tank was covered with a lid and nitrogen gas was supplied to create an inert gas atmosphere in the tank. This mixture was wet-milled for 3.2 hours using a bead mill (MSC Mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd.) to obtain a nanosilicon-containing slurry 14 in which nanosilicon was uniformly dispersed in the dispersion medium. The diameter of the beads in the bead mill was 0.2 mm, and the peripheral speed of the bead mill was 18 m / s. A negative electrode active material was produced using the nanosilicon-containing slurry 14 in the same manner as in Example 1, and evaluations of half cells and full cells were performed. The results are shown in Tables 2 and 3.

[0140] Example 15 Wet milling was performed in the same manner as in Example 4, except that the peripheral speed and milling time during wet milling with a bead mill were changed as shown in Table 2, and an MSC mill MSC220 manufactured by Nippon Coke & Engineering Co., Ltd. was used as the bead mill, to produce nanosilicon-containing slurry 15. A negative electrode active material was produced using this nanosilicon-containing slurry 15. A half cell was evaluated using this in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0141] Examples 16-17 Wet milling was performed using a bead mill in the same manner as in Example 2, except that the milling time during wet milling using a bead mill and the total integrated power per unit weight were changed as shown in Tables 2 and 3, to prepare nanosilicon-containing slurry 16-17. A negative electrode active material was prepared using this nanosilicon-containing slurry 16-17. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0142] Example 18 Except for changing the amount of DISPERBYK9077 to 10 g, wet grinding was performed using a bead mill in the same manner as in Example 4 to prepare nanosilicon-containing slurry 18. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0143] Comparative Example 1 In the first stage of silicon pulverization, the bead diameter during wet pulverization using a bead mill was 0.7 mm, the pulverization time was 6 hours, and the second stage of silicon pulverization was not performed. In the same manner as in Example 1, except that, wet pulverization using a bead mill was performed to prepare nanosilicon-containing slurry 19. A negative electrode active material was prepared using this nanosilicon-containing slurry 19. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0144] Comparative Example 2 In the first stage of silicon pulverization, the bead diameter during wet pulverization using a bead mill was 1.0 mm, and the pulverization time was 3.5 hours, in the same manner as in Example 2, to produce a nanosilicon-containing slurry 20. A negative electrode active material was produced using this nanosilicon-containing slurry 20. Using this, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0145] Comparative Example 3-4 Wet grinding was performed using a bead mill in the same manner as in Example 4, except that the conditions for the first and second silicon grinding steps were changed as shown in Table 2, to prepare nanosilicon-containing slurries 21-22. A negative electrode active material was prepared using the nanosilicon-containing slurries 21-22. Using the negative electrode active material, half-cell and full-cell evaluations were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.

[0146] [Table 1]

[0147] [Table 2]

[0148] [Table 3]

[0149] From Tables 1 to 3 above, it was confirmed that when nanosilicon having an (i) / (ii) ratio of 0.4 or more and silicon raw material are used with beads of 0.5 mm or less and wet-milled under conditions of an integrated input power per weight of 7500 kWh / t or more, the battery capacity retention rate and initial efficiency are generally high and the balance between them is excellent, making them useful as a high-performance negative electrode active material.

[0150] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2023-111323) filed on July 6, 2023, the contents of which are incorporated herein by reference.

Claims

1. 29 In Si-NMR, the ratio (i) of the area of ​​a peak in the range of -75 to -85 ppm to the total peak area (ii) of the areas of the peaks in the range of -110 to -100 ppm, the peak area in the range of -75 to -65 ppm, the peak area in the range of -40 to -30 ppm, the peak area in the range of -10 to 0 ppm, and the peak area in the range of -20 to -10 ppm [(i) / (ii) ratio]] is 0.4 or more.

2. The nanosilicon according to claim 1 after sintering. 29 In Si-NMR, Nanosilicon having a ratio (iii) of the area of ​​the peak in the range of -110 to -100 ppm to the total peak area (iv) of the peak areas in the ranges of -75 to -85 ppm and -95 to -85 ppm [(iii) / (iv) ratio] of 0.4 or less.

3. 2. The nanosilicon according to claim 1, wherein a part of the oxide film on the outer surface of the nanosilicon is amorphous, and the maximum thickness of the oxide film is less than 20 nm.

4. The nanosilicon according to claim 1, wherein the degree of crystal orientation of the (111) plane is 0.25 or more.

5. A nanosilicon-containing slurry comprising the nanosilicon according to any one of claims 1 to 4 and a dispersion liquid.

6. An active material for secondary batteries comprising the nanosilicon according to any one of claims 1 to 4.

7. A method for producing a nanosilicon-containing slurry, comprising wet-pulverizing a silicon raw material to obtain a nanosilicon-containing slurry, wherein beads of 0.5 mm or less are used in the wet-pulverization, and the cumulative input power per weight during the wet-pulverization is 7500 kWh / t or more.

8. The method for producing a nanosilicon-containing slurry according to claim 7, wherein the wet grinding is carried out in two or more stages by changing the bead diameter, and the ratio (D1 / D2) of the initial bead diameter D1 to the bead diameter D2 of the second or subsequent stages is 1.5 or more.

9. The specific surface area of ​​the silicon raw material is 30 m 2 The method for producing a nanosilicon-containing slurry according to claim 7 or 8, wherein the nanosilicon-containing slurry has a molecular weight of 1000 or less.

10. The true density of the beads is 6.5 g / cm 3 The method for producing a nanosilicon-containing slurry according to claim 7 or 8, wherein:

11. The method for producing a nanosilicon-containing slurry according to claim 7 or 8, wherein the volumetric filling rate of the beads in the bead mill in the wet grinding is 50 to 95%.

12. The method for producing a nanosilicon-containing slurry according to claim 7 or 8, wherein the peripheral speed of the bead mill in the wet pulverization is less than 20 m / s.

13. The method for producing a nanosilicon-containing slurry according to claim 7 or 8, wherein the wet pulverization is carried out at a bead mill integrated input power per unit amount of silicon raw material in the range of 7500 kWh / t to 45000 kWh / t.

14. A method for producing an active material for a secondary battery, comprising drying a mixture containing nanosilicon obtained by the method for producing a nanosilicon-containing slurry according to claim 7 or 8 and a resin, and firing the mixture in an inert gas atmosphere to obtain an active material for a secondary battery.

Citation Information

Patent Citations

  • sioc composite electrode material

    JP2018502029A

  • Silicon or silicon alloy, composite active material for lithium secondary battery containing the same, and manufacturing method thereof

    JP2021180124A

  • Sioc structure and composition for negative electrode using same, negative electrode, and secondary battery

    WO2020179409A1